Simulation Methods in Acute Stroke Treatment: Current State of Affairs and Implications. Issue 7 (July 2020) - Kurz, Martin W.; Ospel, Johanna M.; Advani, Rajiv; Sandset, Else Charlotte; Aamodt, Anne Hege; Tennøe, Bjørn; Ersdal, Hege L.; Fjetland, Lars; Ajmi, Soffien; Kurz, Kathinka D.; Goyal, Mayank
Abstract : Supplemental Digital Content is available in the text.